Comparison of five different methods for determining pile bearing capacities - Jaromin, David; Hendrix, Joshua; Long, James H. (Wisconsin Highway Research Program, 2009)
The purpose of this study is to assess the accuracy and precision with which five methods can predict axial pile capacity. The methods are the Engineering News formula currently used by Wisconsin Department of Transportation (WisDOT), the FHWA-Gates formula, the Pile Driving Analyzer, the method developed by the Washington State DOT (WSDOT), and further analysis conducted on the FHWA-Gates method to improve its ability to predict axial capacity. Improvements were made by restricting the application of the formula to piles with axial capacity less than 750 kips, and by applying adjustment factors based on the pile being driven, the hammer being used, and the soil into which the pile is being driven. Two databases of pile driving information and static or dynamic load tests were used to evaluate these methods. Analysis is conducted to compare the impact of changing to a more accurate predictive method, and incorporating load and resistance factor design (LRFD). The results of this study indicate that a ?corrected? FHWA-Gates and the WSDOT formulas provide the greatest precision. Using either of these two methods and changing to LRFD should increase the need for foundation(geotechnical) capacity by less than 10 percent.
176 p.
Keywords: Precision; Piles (Supports); Pile driving; Mathematical prediction; Load tests; Formulas; Bearing capacity; Accuracy